Assessment of Awareness of Local Anaesthetic Systemic Toxicity (LAST) among Postgraduate Trainees - Shafiq Ali Jamaleddin Surani; Maryam Budiman; Mawaddah Azman; Raha Abdul Rahman (International Journal of Clinical Practice)
Introduction. Although uncommon, local anaesthetic systemic toxicity (LAST) may impose fatal risk to the patients. We investigated the awareness of LAST and knowledge on local anaesthetics among our postgraduate trainees. Materials and Methods. A total of 134 postgraduate trainees from the departments of general surgery (Surgical), orthopaedic surgery (Ortho), otorhinolaryngology (ENT), obstetrics and gynaecology (OBGYN), as well as anaesthesiology and intensive care (Anaesth) were recruited. A validated questionnaire was used to assess awareness and knowledge. All participants attended a medical-education session and completed the questionnaire as preassessment and postassessment. Data were analysed, and comparisons between disciplines were conducted. Results. The trainees’ awareness of LAST was overall poor at preassessment which improved almost 6-folds at postassessment. Surprisingly, only 20 (45.5%) participants from the anaesthesiology group had awareness of LAST at preassessment, and none of the participants were from surgical, orthopaedic, and obstetrics and gynaecology departments. Preassessment scores were significantly higher in the anaesth group as compared to all other groups; with a difference in the average score for Anaesth vs Surgical of 3.46 (95%, CI:2.17, 4.74), Anaesth vs Ortho of 3.64 (95%, CI:2.64, 4.64), Anaesth vs ENT of 3.43 (95%, CI:2.20, 4.67), and Anaesth vs OBGYN of 6.93 (95%, CI:5.64, 8.21). However, there was no significant difference of awareness scores between all participants at postassessment scores. Conclusion. The overall level of awareness was poor. However, the implementation of an education session significantly improved the knowledge and awareness across all disciplines.